Online training: The application of the Society 5.0 concept - Michael (IOP conference series. Earth and environmental science, 2021)
Society 5.0 has been introduced, and technology has played an essential role in achieving the aim of improving the prosperity of human beings. Businesses that often provide training to their employees must adapt to how the training course is conducted. While most training courses are conducted face-to-face, online training courses with technology utilization must be considered. Thus, this research intends to look at the effectiveness of online training in the context of Business English training and the perspectives of the subjects on online training methods. Mixed methods research was conducted with 30 subjects in total. A pre-test and a post-test were administered to investigate the effectiveness, and a questionnaire was distributed to explore the subjects’ perspectives. The results have shown that online training is effective as the test results show a dramatic increase. In addition, the subjects also state their approval of training via online methods.